Nancy Fallows,Jackye McClure and Sandy Davis - Unknown:::Creator::::::::::::
Photograph shows group portrait (left to right): Nancy Fallows, Jackye McClure and Sandy Davis possibly at a Rape Crisis Center event. The sign on the podium behind the women reads: "Hya[tt] Regen[cy] in Burlinga[me]." The plaque held by Jackye probably honors her work on behalf of rape victims.